Model Pembelajaran Project Based Learning dalam Meningkatkan Hasil Belajar dalam Aspek Psikomotor dan Sikap pada Mata Pelajaran Jaringan Dasar untuk Siswa Kelas X - Fazri, Agus (Jurnal Inovasi dan Teknologi Pendidikan, 2022)
Basic network subject is productive subject in computer and network engineering major. In the learning process,the teacher wants the student to be able to master not only cognitive but also psychomotor and attitude ability. To solve the problem, the teacher apply Project Based Learning. The goal of the research is to measure the result from psychomotor and affective aspect in Project Based Learning. The research method used is descriptive qualitative method by using questioner and observation during learning in class. Based on the results of the study, it was found that work attitude became the highest psychomotor aspect of 86.30% and work results became the smallest aspect of 74.10%. Meanwhile, other aspects have met the minimum completeness, namely, work preparation of 84.30%, work process of 77.00% and implementation time of 78.60%. The value of the Cooperation aspect is 85.10% better than other aspects, while the confidence aspect is the smallest aspect of 76.20%. Meanwhile, for other aspects, satisfactory results were obtained, for aspects of manners 78.10%, discipline 80.70%, and responsibility 76.90%